PENYULUHAN LEGALITAS HAK KEPEMILIKAN MEREK PRODUK UMKM DI DESA WISATA ROTAN, TRANGSAN, GATAK, SUKOHARJO - Rifzal Alief Ramadhan, Muhammad; Rashed, Azhar; Wira Buana, Adiatama (CV. Lafadz Jaya, 2025)
Trademarks are used by brand owners based on trademark rights obtained according to each country’s regulations. Trademark rights are not an absolute monopoly and have a time limit. These rights can only be used by the owner or authorized parties. Indonesia applies the first-to-file system to ensure legal certainty for brand owners. However, many businesses are unaware of the importance of trademark registration, leading to frequent violations of both registered and unregistered trademarks. In contrast, the United States follows the use in commerce system, which provides protection even for unregistered trademarks. Trademark infringement cases often arise when a product goes viral, and other businesses use similar branding without authorization, leading to legal disputes and economic losses. Legal awareness regarding Intellectual Property Rights remains low in Indonesia. Trademark registration is crucial for businesses, especially MSMEs, to gain legal protection and exclusive rights under Law No. 20 of 2016 concerning Trademarks. Community Service activities related to legal counseling on MSME product brand ownership in Rattan Tourism Village, Trangsan, Gatak, Sukoharjo, aim to enhance legal knowledge and awareness among MSME business actors.